2020
DOI: 10.2337/cd19-0077
|View full text |Cite
|
Sign up to set email alerts
|

Review of Associations Between Type 2 Diabetes and Cancer

Abstract: Debate is ongoing regarding the relationship between type 2 diabetes and cancer, and the pathways linking the two are incompletely understood. Some posit that the relationship hinges on a common predisposing factor such as obesity, insulin resistance, or chronic inflammation that increases the risk of cancer independently. Others speculate that diabetes acts as an independent risk factor for cancer because of other molecular pathways and interactions. Additionally, antidiabetic medications have been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
1
7
0
2
Order By: Relevance
“…CRC is one of the most diagnosed cancers globally [ 48 ], with an increasing number of cases in recent decades [ 49 ]. In addition, T2D was associated with an increased incidence and prevalence of CRC, as hyperglycaemia is thought to have a significant role in the proliferation and expansion of colorectal cancer cells [ 50 ]. The influence of probiotic supplements on CRC is twofold.…”
Section: Resultsmentioning
confidence: 99%
“…CRC is one of the most diagnosed cancers globally [ 48 ], with an increasing number of cases in recent decades [ 49 ]. In addition, T2D was associated with an increased incidence and prevalence of CRC, as hyperglycaemia is thought to have a significant role in the proliferation and expansion of colorectal cancer cells [ 50 ]. The influence of probiotic supplements on CRC is twofold.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, both obesity and diabetes became highly prevalent worldwide [ 2 , 142 ]. Both of them are associated with elevated risk of cancer incidence and mortality [ 17 , 18 , 20 ]. Antidiabetic medications can modulate this risk via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The methods and effectiveness of diabetes therapy and monitoring have also changed over the years, which has extended the life span of patients and also extended the time window for the development of malignant cancers in this population. Therefore, only the recent epidemiological data, published in this century, has given a more complete picture and documented a significantly higher incidence of certain cancers in people with diabetes, as well as with obesity [ 17 , 18 , 19 , 20 ]. In the last years, also the problem of oncological safety as well as oncoprotective properties of antidiabetic medications has become the subject of extensive discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies on HbA1c levels and cancer mortality have also been conflicting. Multiple studies have reported that HbA1c level is associated with an increased risk of poor cancer outcomes at several anatomical sites, including the breast and colon [ 15 , 16 , 17 , 18 ]. A study conducted among Singaporean Chinese also reported that HbA1c was related to cancer mortality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%